2021
DOI: 10.18844/cjes.v16i4.6033
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of principals’ supervision competence through accompaniment in principal working groups

Abstract: A principal’s supervision competency affects the improvement in the teaching and learning process; therefore, it needs to be improved. This study aimed to describe the principal working group (PWG) activities and the principal’s supervision competencies after being assisted by school supervisor in the PWG at Sangkuang Island, East Kutai Regency. This research used a qualitative method and was conducted at state elementary schools. Data collection used interview, observation and documentation techniques. The da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
6
0
4
Order By: Relevance
“…In general, the solutions to overcome these obstacles are 1) the supervisor and the teacher choose learning methods and media that are in accordance with the material and characteristics of the students; 2) looking for the right strategy in classroom management such as seating arrangements for students, dividing students into several groups so that the learning process is more organized and comfortable; 3) the material presented is made interesting and fun so that students are excited and enthusiastic about learning which in the end there is good interaction between teachers and students; 4) the teacher provides the widest opportunity for students to discuss, argue, and ask questions about the material being studied and provide reinforcement to students so that learning becomes more meaningful; and 5) the teacher gives awards to students who have followed the lesson well so that it is hoped that this will motivate students to further improve their learning achievement. Nurlaili et al, (2021) revealed that academic supervision can be interpreted as a face-to-face meeting process between supervisors and teachers, discussing teaching in the classroom to improve learning and professional development through collegial or peer-to-peer methods between supervisors teachers. Academic supervision, according to Kusrini et al, (2018) is a form of supervision that is focused on improving teaching by means of a systematic cycle of planning, observation, and intellectual and intensive analysis of real teaching performances, in making changes in a rational way.…”
Section: Catholic Religion Teachermentioning
confidence: 99%
“…In general, the solutions to overcome these obstacles are 1) the supervisor and the teacher choose learning methods and media that are in accordance with the material and characteristics of the students; 2) looking for the right strategy in classroom management such as seating arrangements for students, dividing students into several groups so that the learning process is more organized and comfortable; 3) the material presented is made interesting and fun so that students are excited and enthusiastic about learning which in the end there is good interaction between teachers and students; 4) the teacher provides the widest opportunity for students to discuss, argue, and ask questions about the material being studied and provide reinforcement to students so that learning becomes more meaningful; and 5) the teacher gives awards to students who have followed the lesson well so that it is hoped that this will motivate students to further improve their learning achievement. Nurlaili et al, (2021) revealed that academic supervision can be interpreted as a face-to-face meeting process between supervisors and teachers, discussing teaching in the classroom to improve learning and professional development through collegial or peer-to-peer methods between supervisors teachers. Academic supervision, according to Kusrini et al, (2018) is a form of supervision that is focused on improving teaching by means of a systematic cycle of planning, observation, and intellectual and intensive analysis of real teaching performances, in making changes in a rational way.…”
Section: Catholic Religion Teachermentioning
confidence: 99%
“…Unsur-unsur yang supervisi akademik kepala sekolah mencakup perencanaan pembelajaran, pelaksanaan pembelajaran, dan evaluasi pembelajaran (Ding & Swalwell, 2018). Kepala sekolah mampu merencanakan program supervisi dengan baik, melakukan supervisi standar dan melaksanakan supervisi lanjutan sesuai kebutuhan (Amon & Harliansyah, 2022;Nurlaili et al, 2021).…”
Section: Pendahuluanunclassified
“…Unsur-unsur yang supervisi akademik kepala sekolah mencakup perencanaan pembelajaran, pelaksanaan pembelajaran, dan evaluasi pembelajaran (Ding & Swalwell, 2018). Kepala sekolah mampu merencanakan program supervisi dengan baik, melakukan supervisi standar dan melaksanakan supervisi lanjutan sesuai kebutuhan (Nurlaili et al, 2021).…”
Section: Pendahuluan *unclassified